Comparison of BO Regeneration Dynamics in PERC and Al-BSF Solar Cells. (August 2015) - Herguth, Axel; Horbelt, Renate; Wilking, Svenja; Job, R.; Hahn, Giso
Abstract: Boron-oxygen related lifetime degradation is a severe problem for high-efficiency solar cells as the applied concepts like PERC suffer strongly from the observed lifetime degradation. However, these efficiency losses can be avoided via the Regeneration process eliminating the harmful defects. Within this contribution the effect of device structure on Regeneration kinetics is investigated. It is found that PERC-type cells regenerate faster than full area Al-BSF-type cells. It is pointed out why PERC-type cells benefit from an injection level effect. But this effect is not the only reason for the accelerated Regeneration. By means of especially adapted PERC cells, which do not benefit from the injection level advantage, it is shown that a second hydrogen containing layer on the rear has a positive influence, too, probably due to an increased hydrogenation of the silicon bulk.